The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1074/jbc.273.29.18205
|View full text |Cite
|
Sign up to set email alerts
|

The Human Homolog of Saccharomyces cerevisiae CDC45

Abstract: In budding yeast Saccharomyces cerevisiae CDC45 is an essential gene required for initiation of DNA replication. A structurally related protein Tsd2 is necessary for DNA replication in Ustilago maydis. We have identified and cloned the gene for a human protein homologous to the fungal proteins. The human gene CDC45L is 30 kilobases long and contains 15 introns. The 16 exons encode a protein of 566 amino acids. The human protein is 52 and 49.5% similar to CDC45p and Tsd2p, respectively. The level of CDC45L mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 30 publications
(31 reference statements)
4
27
1
Order By: Relevance
“…The transcripts for CDC45 are upregulated at the G1/S transition, as has been shown in other organisms (Saha et al, 1998). Although this finding does not give an indication of the level of protein activity during the cell cycle, it indicates that CDC45 may be one of a number of genes important in the G1/S transition.…”
Section: Cdc45 In Mitosismentioning
confidence: 60%
“…The transcripts for CDC45 are upregulated at the G1/S transition, as has been shown in other organisms (Saha et al, 1998). Although this finding does not give an indication of the level of protein activity during the cell cycle, it indicates that CDC45 may be one of a number of genes important in the G1/S transition.…”
Section: Cdc45 In Mitosismentioning
confidence: 60%
“…Experiments in Xenopus egg extract, budding yeast, fission yeast, and human cells have shown that loading of Pol␣-primase onto chromatin and replication origin requires Cdc45 (1,22,26,40,47). In addition to Pol␣-primase, Cdc45 also associates with ORC/Orp, RPA, Polε, and the MCM complex (21,22,34,38,39,43,47). Together, these studies suggest that Cdc45 plays a critical role in coordinating origin sequence unwinding by MCMs and initiation of DNA synthesis by Pol␣-primase.…”
mentioning
confidence: 75%
“…In addition to the genes already mentioned, mammalian homologs of CDC7 and CDC45 genes have also been recently identified and shown to be expressed in a cell growth-regulated manner with a peak at the G1/S boundary (135)(136)(137)(138). While the protein level of HsCdc45 is constant throughout the cell cycle in cycling HeLa cells (138), promoter analyses have demonstrated that growth-regulated expression of the gene is essentially mediated by E2F sites in the promoter region (unpublished data).…”
Section: Regulatory Machinery For Dna Replicationmentioning
confidence: 99%
“…While the protein level of HsCdc45 is constant throughout the cell cycle in cycling HeLa cells (138), promoter analyses have demonstrated that growth-regulated expression of the gene is essentially mediated by E2F sites in the promoter region (unpublished data).…”
Section: Regulatory Machinery For Dna Replicationmentioning
confidence: 99%